THE ANALYSIS OF THE PROBLEM OF CORROSION OF CEMENT CONCRETE IN ATMOSPHERIC CONDITIONS AND THE ROLE OF WATER IN THIS PROCESS - Kolesnyk, D. Yu.; Sychenko, V. H.; Koval, P. M. (Science and Transport Progress, 2006)
The surveying article is devoted to generalization of the published lately works devoted to chemical corrosion of concrete. The attempt of exposure of basic conformities to the law of degradation of cement stone and participation in this process of carbon dioxide, chlorides, sulfates and water is done. Offered ways of increase of аtmospheric stability of concrete by the method of his second defence.